2014
DOI: 10.1111/ffe.12163
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of fatigue crack growth resistance by controlled overaging in 2024‐T3 aluminium alloy

Abstract: A B S T R A C T A controlled overaging process is proposed to increase region II fatigue crack propagation resistance of 2024-T3 aluminium alloy. Overaging was achieved by subjecting the material from the initial T3 state to heat treatment at specific aging temperatures resulting in substantial reduction in hardness. Fatigue crack growth tests were subsequently performed in the intermediate ΔΚ region to assess the influence of aging treatment on fatigue crack propagation rate. The experimental results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 22 publications
(50 reference statements)
1
36
0
Order By: Relevance
“…The roughness data shown in Table infers that the fracture surface roughness is relatively high in RRA compared with T6 alloy suggesting higher closure in RRA leading to reduced crack growth rates. A similar observation of enhanced fatigue crack growth resistance was observed in Al‐Cu systems which was attributed to increased cyclic strain hardening, leading to higher closure levels in over aged condition …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The roughness data shown in Table infers that the fracture surface roughness is relatively high in RRA compared with T6 alloy suggesting higher closure in RRA leading to reduced crack growth rates. A similar observation of enhanced fatigue crack growth resistance was observed in Al‐Cu systems which was attributed to increased cyclic strain hardening, leading to higher closure levels in over aged condition …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been made on the effect of heat treatment on the fatigue crack growth behavior of various aluminum alloys. The studies made on 2xxx series aluminum alloys have shown that over aging imparts enhanced fatigue crack growth resistance . This has been attributed to cyclic strain hardening response of Al‐Cu systems in over aged condition that promotes higher crack closure, which is reported to benefit low cycle fatigue behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the strain hardening contributes to increased COS. The Tzamtzis research is available to support this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue behaviour of various aluminium alloys and their different chemical compositions have been studied extensively. Studies mainly focused on the different fatigue behaviour of different aluminium alloys, while few of them focused on specimens under low cycle fatigue and high cycle fatigue . Numerous studies regarding the fatigue life of various aluminium alloys under different temperatures have been conducted.…”
Section: Introductionmentioning
confidence: 99%